Illocutionary Speech Act (Analysis in Arabic Animated Series “SFH Youtube Channel”) - Ahmad Habibi Syahid; Saphira Zulfan Hadi; Nuroh Nuroh (Uktub: Journal of Arabic Studies, 2023)
This study is illocutionary speech acts performed in Arabic animated series in Youtube channel. This study aims to describe the types as well as the functions of illocutionary speech acts performed by characters in the animated series SFH Youtube Channel. Moreover, this study also describes the most and the least used illocutionary speech acts performed in the movie. This study uses qualitative method employing descriptive analysis design. The data sources of this research were collected by watching animated series videos from YouTube and then observing them transcribing speech acts in the video in written form. Furthermore, the data are categorized into some types of illocutionary speech acts. The result showed that there are five kinds of illocutionary speech acts which are performed in Arabic animated series "SFH Youtube Channel" which are representative, declarative, expressive, directive, and commissive.